Analysis of Leveraging Factors in Socio-Cultural Dimension Aspects for Sustainable Mangrove Forest Management in Aluh Aluh Besar Village, Banjar Regency - Jaya, Eddy Elminsyah (Agrikan Jurnal Agribisnis Perikanan, 2024)
Banjar Regency is a Regency in South Kalimantan Province which is recorded as having a mangrove forest area. One of the villages that has mangrove forest potential is Aluh Aluh Besar Village. The aim of this research is to analyze leveraging factors in the context of sustainable mangrove forest management in the socio-cultural dimension. This research uses a quantitative and qualitative approach with a longitudinal design because it is sustainable over a relatively long period of time and follows an interactive process of various variables. The research results show that the largest leverage factor is â€œOwnership Statusâ€ with a value of 2.04 and the lowest is Environmental Knowledge (0.05). To measure sensitivity, a leverage analysis was carried out using 10 (ten) attributes. The conclusion of the research conducted shows that "Ownership Status" is the biggest lever in maintaining the sustainability of mangrove forests in the research location. "Ownership Status" is important because it is based on the causes of land conversion or conversion resulting from the transfer of ownership from the community to investors or the community itself. convert it to other economic activities. Land owners feel they have rights to the area they own. One important policy is to ensure ownership of land on which mangrove forests are "owned by the government". Apart from efforts to raise public awareness of the importance of mangrove forests to support the lives of local communities. LoA, Kor